Pemberdayaan Masyarakat dalam Meningkatkan Mutu Pendidikan Non-Formal: Studi Kasus di PKBM Al-Suraya Kota Metro - Lampung - Dacholfany, M Ihsan (Tapis: Jurnal Penelitian Ilmiah, 2018)
The non-formal education of an education service that is not limited by age, time, gender, race (ethnicity, descent), economy, socio-cultural conditions, religion and so on, although formal education is an essential component of lifelong education, Informal education in the framework of lifelong educational services for the community is needed now and in the future. Herewith the Researcher uses analytic descriptive method with case study variation. Descriptive analytic method is a method of research that emphasizes the effort to obtain information about the status or symptoms at the time of the study, provide an overview of the phenomena, also further explain the relationship, and draw the meaning of a desired problem. The research in Learning centers al-Suroya in which there is Non Formal Education which is carried out especially Package B and Package C and others can fulfill a function in the effort to serve the needs of society outside the school system, the main target of non formal education and is needed by the community especially the people who want Continuing education, as well as developing the ability of interest and talent as well as training, in the hope that this program is implemented in accordance with the ability of the community despite many obstacles.